The equivalent slab thickness of Mars' ionosphere: Implications for thermospheric temperature. Issue 9 (5th May 2015) - Mendillo, M.; Narvaez, C.; Lawler, G.; Kofman, W.; Mouginot, J.; Morgan, D.; Gurnett, D.
Abstract The total electron content (TEC) of a planetary ionosphere is dominated by plasma near and above the height of maximum electron density (Nmax). The ratio TEC/Nmax represents the thickness (τ) of a TEC slab of uniform density (Nmax). For a photochemical ionosphere, τ relates to the scale height (H = kT/mg) of the ionized neutral gas as τ 4 × H. Derived temperatures refer to 160 km in thermosphere height—below the asymptotic temperature of the exosphere. The MARSIS instrument on Mars Express has produced data sets of TEC and Nmax. We used them to form τ patterns versus solar zenith angle and solar cycle phase. For daytime (SZA < 90°) conditions, <τ > day 50 km, decreasing rapidly for solar zenith angle (SZA) > 90° to < τ > night 25 km. These correspond to Tn values of 250°K and 125°K. Using Mars Global Surveyor data, τ patterns show a mild dependence upon the solar EUV flux proxy F10.7, with ΔTn(°K) 0.3° per unit change in F10.7 at Mars.